Extrapulmonary Surfactant Therapy: Review of Available Data and Research/Development Issues. (23rd June 2020) - Foligno, Silvia; Loi, Barbara; Pezza, Lucilla; Piastra, Marco; Autilio, Chiara; De Luca, Daniele
Abstract: Since the discovery of surfactant, a large amount of knowledge has been accumulated about its biology and pharmacology. Surfactant is the cornerstone of neonatal respiratory critical care, but its proteins and phospholipids are produced in various tissues and organs, with possible roles only partially similar to that played in the alveoli. As surfactant research is focused mainly on its respiratory applications, knowledge about the possible role of surfactant in extrapulmonary disorders has never been summarized. Here we aim to comprehensively review the data about surfactant biology and pharmacology in organs other than the lung, especially focusing in the more promising surfactant extrapulmonary roles. We also review any preclinical or clinical data available about the therapeutic use of surfactant in these contexts. We offer a summary of knowledge and research/development milestones, as possible useful guidance for researchers of multidisciplinary background.